2019
DOI: 10.1002/1878-0261.12485
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CHIP promotes ovarian cancer metastasis by inducing Snail‐mediated epithelial–mesenchymal transition

Abstract: The epithelial–mesenchymal transition (EMT) plays a pivotal role in the conversion of early‐stage tumors into invasive malignancies. The transcription factor Snail, an extremely unstable protein whose subcellular levels are regulated by many E3 ubiquitin ligases, promotes EMT as well as associated pathological characteristics including migration, invasion, and metastasis. Through yeast two‐hybrid screening, we identified the carboxyl terminus of Hsc70‐interacting protein (CHIP) as a novel Snail ubiquitin ligas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“… 15 STUB1 suppressed stemness and tumorigenicity of oral carcinoma cell, 16 and downregulation of STUB1 promoted epithelial-mesenchymal transition of ovarian cancer. 17 Recent study has shown that STUB1 was aberrantly expressed in breast cancer, 18 and STUB1 promoted ubiquitin/proteasome-dependent degradation of ERBB2-mediated oncogenes in breast cancer. 19 Our results showed that over-expression of STUB1 attenuated TRIM6-induced increase in breast cancer cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“… 15 STUB1 suppressed stemness and tumorigenicity of oral carcinoma cell, 16 and downregulation of STUB1 promoted epithelial-mesenchymal transition of ovarian cancer. 17 Recent study has shown that STUB1 was aberrantly expressed in breast cancer, 18 and STUB1 promoted ubiquitin/proteasome-dependent degradation of ERBB2-mediated oncogenes in breast cancer. 19 Our results showed that over-expression of STUB1 attenuated TRIM6-induced increase in breast cancer cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…SPSB3 targets SNAI1 to promote polyubiquitination and degradation in response to GSK3β phosphorylation of SNAI1. Through yeast two-hybrid screening, the carboxyl terminus of Hsc70-interacting protein (CHIP) was identified as a novel SNAI1 ubiquitin ligase that interacts with SNAI1 to induce ubiquitin-mediated proteasomal degradation [49]. Recently, it was reported that SNAI1 was monoubiquitinated by the ubiquitin-editing enzyme A20.…”
Section: Ubiquitination and Deubiquitinationmentioning
confidence: 99%
“…Besides, the expression of SNAIL is associated with cancer metastasis. It has also been observed that SNAIL expression levels are elevated in distant metastasis originating from ovarian cancer [ 175 , 176 ]. A recent study revealed that SNAIL-induced EMT accelerates metastasis through induction of immune suppression [ 161 , 177 ].…”
Section: Myc–the Regulator Of Emt and Metastasismentioning
confidence: 99%